Long-Term Treatment Strategies of Pediatric Multiple Sclerosis, Including the use of Disease Modifying Therapies - Mary Rensel (MDPI AG, 2019)
Multiple sclerosis (MS) presenting in the pediatric years can lead to landmark disability levels younger in life than adult onset MS and so therefore early and effective treatment remains paramount for long-term outcomes. The goals of MS therapeutics in adults have widened to address multiple mechanisms: anti-inflammatory, neuroprotective, and myelin repair, yet the optimal paradigm for MS therapies in the pediatric population is not known. Pediatric onset MS add complexities due to the ongoing development of the central nervous system and the immune system. Clinical trials have led to an increasing number of pharmaceutical therapies for adult onset MS (AOMS), one POMS randomized controlled trial is completed and other trials are ongoing, yet due to the low prevalence of POMS, the dynamic landscape and risk management of the MS disease modifying therapies (DMT) it remains more difficult to complete trials in POMS. There is consensus that controlled clinical trials leading to appropriate and safe therapies for POMS are important for a multitude of reasons that include unique pediatric pharmacokinetics, short and long-term safety, developmental issues, clinical benefits, and regulatory approval. This review will focus on new treatment goals, paradigm, strategies, monitoring, compliance, and products in the long-term treatment of POMS. The discussion will focus on these new concepts and the published data related to DMT use in POMS. This review provides significant insight into new concepts of treatment goals and current approaches to enhance the lives of the POMS patients now and in the future.